RELATIONSHIP BETWEEN FAMILY LIFE -STYLE AND NUTRITIONAL STATUS AMONG KINDERGARTEN CHILDREN IN NINEVAH GOVERNORATE - Refai Yassen Al-Hussein; Ashraf Elias Khudhair Kano (College of Nursing,University of Mosul, 2018)
A descriptive study was carried out to determine relationship between family life-style and nutritional status among kindergarten children in Nineveh Governorate for the period 25th December/ 2006 to 29th March /2007. The sample of the study consisted of (450) child. The data were collected by using questionnaire and checking the BMI (Wt/Ht2). The result of the study indicated that there are some significant differences between life-style and variables undertaken in the study. There are also highly significant differences between BMI and the variables. Consequently, the study concluded that family life-style reflects obviously on the BMI of the children. The study recommends that parents and families may pay attention to their life-style and make healthy modifications.